KANITA – THE FIRST RESEARCH CENTRE ON GENDER IN THE COUNTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 March 2016 – Being the first centre of excellence to be established in Malaysia in 1978 that focuses on gender research, the Centre for Research on Women and Gender (KANITA) Universiti Sains Malaysia (USM) plans to have more research on women and genderrelated issues, as there is still plenty to study and to collaborate in with international institutions.